2009
DOI: 10.1051/0004-6361:200810965
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of 2006 RH120: an asteroid temporary captured into a geocentric orbit

Abstract: Aims. From July 2006 to July 2007 a very small asteroid orbited the Earth within its Hill sphere. We used this opportunity to study its rotation and estimate its diameter and shape. Methods. Due to its faintness, 2006 RH 120 was observed photometrically with the new 10-m SALT telescope at the SAAO (South Africa). We obtained data on four nights: 11, 15, 16, and 17 March 2007 when the solar phase angle remained almost constant at 74• . The observations lasted about an hour each night and the object was exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…The Light Curve Data Base 1 (LCDB), described in Warner et al (2009) Recently new periods were reported for four very small NEAs by Birtwhistle (2009) (Kwiatkowski et al 2009), 13 fast-rotating NEAs (Paper I), and another 12 objects from the near-Earth asteroid population (this paper). We also revised the period of 2006 XY, which is already included in the LCDB, and which we discussed in Paper I.…”
Section: Summary Of the Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The Light Curve Data Base 1 (LCDB), described in Warner et al (2009) Recently new periods were reported for four very small NEAs by Birtwhistle (2009) (Kwiatkowski et al 2009), 13 fast-rotating NEAs (Paper I), and another 12 objects from the near-Earth asteroid population (this paper). We also revised the period of 2006 XY, which is already included in the LCDB, and which we discussed in Paper I.…”
Section: Summary Of the Resultsmentioning
confidence: 80%
“…The instruments and the methods of data reduction were described in Kwiatkowski et al (2009), which presents observations of an unusual asteroid 2006 RH 120 . A systematic presentation of the early results of the survey was presented in Kwiatkowski et al (2010) (hereafter Paper I) where we published the lightcurves of a sample of the fastest rotating asteroids (periods shorter than 1 h).…”
Section: Introductionmentioning
confidence: 99%
“…The data were reduced using the same LIDAS package. The lightcurve was analysed by iteratively fitting a Fourier series using different trial periods (Kwiatkowski et al 2009). The best fit was obtained for two synodic periods: P 2 = 4.459 ± 0.003 min and P 3 = 8.917 ± 0.004 min which is quite common in case of noisy lightcurves.…”
Section: Rotation Periodmentioning
confidence: 99%
“…The first object from our campaign has been presented in Kwiatkowski et al (2009). It was an unusual near-Earth asteroid 2006 RH 120 .…”
Section: Introductionmentioning
confidence: 99%